Analisis Sistem Rantai Nilai Komoditas Stroberi Segar (Fragaria × ananassa L.) di Desa Candi Kuning - Novel Pardosi; I Gst Ngr Apriadi Aviantara; I Wayan Widia (Jurnal BETA (Biosistem dan Teknik Pertanian), 2014)
The research aimed to know of the analysis of value chain in the commodity supply chain system of fresh strawberries that occurred in candi kuning village, to know the actors involved in agribusiness commodity strawberries has received the results section that corresponds to the activity in the business . This research was conducted by survey method . In this study, the data obtained in the form of qualitative and quantitative data were analyzed using analysis approach benefit cost ratio. The results of the analysis of the benefit cost ratio showed no difference in the level of feasibility acquired by businesses in the supply chain of commodity strawberries business in Candi Kuning village. Generally all businesses involved in the commodity business activity chain strawberries have a decent profit . The greatest gains received by businesses operators a retail 2:17 benefit most small businesses received by farmers in the amount of 1:27 . Among the three kinds of characteristics of farmers, farmers are able to sell directly to the end consumer commodity earn greater profits in the amount of 1.90 . With the result of the sale to the consumer and the merchant costs incurred on farmers and collectors, then the total benefit cost ratio in the businesses of fresh strawberries in the village of Candi Kuning is at 1:36 in other words activities strawberry growers and collectors strawberries and retailers in the Village Candi Kuning is economic worthy to be done.